Contribution of Foreign Employment and Remittances to Nepalese Economy - Shrestha, Bijaya (NRB Economic Review, 2008)
This paper assesses the contribution of foreign employment and remittances to Nepalese economy and also identifies the information needs and gaps. An attempt is also made to assess the role of remittances in poverty reduction. At a time when the country's major economic indicators are not favorable, the remittances have played a vital role in maintaining macro economic stability and keeping the economy afloat. Though remittances sent home by migrant workers is a boon to the economy, the facilities are inadequate to back up the increasing trend of migration. Inadequate information on foreign employment, lack of skill training and lack of assurance of safe working environment and rights of the migrant workers have obstructed foreign employment. Formulation and effective implementation of pro poor migration policy is the need of today. The government should play a proactive role to promote foreign employment by inducting and adhering to the policy of economic diplomacy. Replicating the best practice of the region has to be endorsed in our national context for promotion and regularization of foreign employment, to encourage official transfer of remittance and to streamline the asset and skill of the returnees for the economic development of the country.